Numerical simulation of the attached growth reactor with different arrangement of bio-balls - Hayder G.; Perumulselum P. (Penerbit Akademia Baru, 2023)
Two different simulations were run using ANSYS CFX to analyze the effect of aeration on the balls and to identify the effect of different arrangement on aeration. From the first simulation, close fin ball arrangement was chosen as the best arrangement because the forces acting on the surface of fin ball and inside the fin ball in this arrangement are optimum. When the forces are too low, the scouring process will not occur which promote thicker and excessive biofilm grow which will lead to clogging while when the forces acting on bio-balls are high, detachment of biofilm from the surface will occur. From the second simulation, loose fin ball arrangement and loose cage ball arrangement were chosen as the best arrangement because there is less blue contours zone which indicates the wastewater saturated faster. 2018 PENERBIT AKADEMIA BARU - All rights reserved.